THE EFFECTIVENESS OF THE BOOKLET ON HENDLING EMERGENCIES DUE TO STINGS FROM VENOMOUS MARINE ANIMALS ON TOURISTS AT TRIKORA BEACH, BINTAN REGENCY - Deliana, Muthia; Dewi Pusparianda; Santa Novita Yosephin Silalahi; Elsa Gusrianti (International Journal of Social Science, 2024)
The high level of beach tourism activities in Indonesia, especially at Trikora Beach, Bintan district, also increases incidents/accidents related to beach activities, including diving, swimming and fishing. One incident that occurs quite often is being stung by venomous marine animals. The need for fast treatment before the victim is transferred to the hospital. Therefore, tourists need adequate knowledge to prevent complications from occurring. The aim of this research is to see the effectiveness of booklet media regarding handling stings from venomous marine animals at Trikora Beach, Bintan district. Quasi experimental research design with a pre and posttest design approach. This research was conducted from June - November 2022 at Trikora Beach, Kawal Health Center working area, Bintan Regency. The population in this study were all tourists who visited Trikora Beach, Bintan Regency in the Kawal Health Center working area. The sample in this study was 68 samples in the intervention group and control group. The research results showed that there was a difference in tourists' knowledge about handling the effects of venomous marine animal stings, with a P-value of 0.003 (< 0.05), so Ho was rejected. And in the control group, the p-value was 0.041 (< 0.05). Conclusion: Media booklet about handling emergencies due to stings from venomous marine animals is effective in increasing tourists' knowledge of this matter. It is hoped that the Kwal Community Health Center can make the booklet one of the service standards in increasing the knowledge of the community, especially tourists, about handling emergencies due to stings from venomous marine animals.